2009
DOI: 10.1188/09.onf.52-60
|View full text |Cite
|
Sign up to set email alerts
|

Use of Buffered Lidocaine in Bone Marrow Biopsies: A Randomized, Controlled Trial

Abstract: Advanced practice nurses perform a significant number of bone marrow biopsies and aim to improve patient comfort during invasive procedures. Use of unbuffered lidocaine should be questioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Some providers elect to use conscious sedation during the bone marrow procedures in an attempt to mitigate procedural pain and discomfort; but this takes longer and may expose the patient to additional physical risks, result in increased liability for the provider, and require increased patient monitoring during and after the procedure [13]. In a study of 138 patients evaluating the effects of lorazepam on pain during bone marrow procedures, Park et al reported mean VAS scores during the bone marrow procedures as 6.0 ± 2.5 for lorazepam vs. 6.2 ± 2.3 for placebo [14].…”
Section: Introductionmentioning
confidence: 99%
“…Some providers elect to use conscious sedation during the bone marrow procedures in an attempt to mitigate procedural pain and discomfort; but this takes longer and may expose the patient to additional physical risks, result in increased liability for the provider, and require increased patient monitoring during and after the procedure [13]. In a study of 138 patients evaluating the effects of lorazepam on pain during bone marrow procedures, Park et al reported mean VAS scores during the bone marrow procedures as 6.0 ± 2.5 for lorazepam vs. 6.2 ± 2.3 for placebo [14].…”
Section: Introductionmentioning
confidence: 99%
“…3 In our study, in which buffered lidocaine was also used, subjects rated their pain at 38.0 on average with the Powered device. When given the opportunity to change the score for the first procedure, the mean pain score for the Powered insertions was reduced to 20.9.…”
Section: Discussionmentioning
confidence: 99%
“…Attempting to mitigate the procedural pain and discomfort, some providers elect to use conscious sedation during the bone marrow procedures; but this may expose the patient to additional physical risks, increased liability to the provider, and a requirement for increased patient monitoring during and after the procedure. 3 …”
Section: Introductionmentioning
confidence: 99%
“…28 A randomized control trial of patients with procedural pain who accepted buffered lidocaine solution or unbuffered preparations for LP biopsy procedures revealed that the former did not make LP biopsy less painful than the latter. 29 In a prospective trial, pretreatment with tramadol plus local injection of 2% lidocaine was reportedly associated with less pain intensity than placebo, thereby indicating that it could be a good local anesthetic for LP biopsy combined with local lidocaine injection. 30 Studies demonstrate that lidocaine administration usually causes mild local skin reactions, such as edema, pallor, or erythema, although other severe complications, such as methemoglobinemia, cardiotoxicity, and central nervous system toxicity, can also be encountered.…”
Section: Discussionmentioning
confidence: 99%